Isolation of embryonic chick motoneurons and their survival in vitro - O'Brien, RJ (J Neurosci, 1986)
This is the first of a series of 4 papers in which we describe the regulation of excitatory amino acid receptors on embryonic chick motoneurons dissociated from the lateral motor column and maintained in cell culture. Techniques are described for labeling embryonic chick motoneurons in vivo with Lucifer Yellow or fluorescein isothiocyanate conjugates of wheat germ agglutinin (Fl-WGA). We estimate that 65–95% of the motoneurons in the lateral motor column survive tissue dissociation and settle on an appropriate culture surface. The number of fluorescent motoneurons observed in heterogeneous spinal cord cell cultures decreases with a half-life of 2 d. The decline is due to fading of the fluorescent tracer rather than to loss of cells. Techniques are also described for separating motoneurons from other spinal cord cells with a fluorescence-activated cell sorter. Approximately 24% of the motoneurons in the lateral motor column can be isolated, and motoneurons comprise more than 90% of the population in cultures seeded with sorted cells. The survival of sorted and unsorted motoneurons in vitro is enhanced in the presence of skeletal myotubes or muscle conditioned medium, but the survival of non-motoneurons is not influenced by muscle. Electrophysiologic properties of sorted and unsorted motoneurons determined with patch-clamp techniques are similar. Both differ from mature motoneurons in their lower resting membrane potential (-50 mV), larger input resistance (450 M omega), and longer time constant (39 msec). Also they do not exhibit anomalous rectification or a calcium-activated potassium after hyperpolarization. Motoneurons grown in the absence of interneurons differ from motoneurons in heterogeneous spinal cord cell cultures in that their neurites (dendrites) are shorter and they branch less often.